An Integrated Model of the Sappãya Principles to Promote Self-Reliance of the Elderly in Doi Saket Subdistrict Municipality, Doi Saket District Chiang Mai Province - Pramchit, Lampoo; Punthiya, Phoonchai; Pannengpetch, Yueng (Academic MCU Buriram Journal, 2023)
The purpose of this research were: 1) to examine the Sappàya principle as found in Theravada Buddhist scriptures, 2) to investigate the concept of Sappàya and Self-Reliance of the Elderly, and 3) to propose an integrated model of the Sappàya. The Sappàya principle was used to analyze field data collected from 31 elderly people and their relatives to learn more about how to encourage elder independence. The research results found that: 1. The Sappàya principle refers to things that are comfortable and supportive in meditating with good results. It consists of seven conditions things viz., 1) suitable abode, 2) suitable resort, 3) suitable speech, 4) suitable person, 5) suitable food, 6) suitable climate and 7) suitable posture. In this study, the concept of Sappàya refers to the convenience of living for the elderly. The principle of self-sufficiency entails not being a burden to others. 2. The Sappàya concept refers to the ease with which the elderly can live. Being self-sufficient means not relying on others for assistance. It may also be able to rely on other people. Buddhism’s self-reliance teachings refer to Dhamma, which serves as reliance. Dhamma fosters a refuge morality that allows for independence. 3. A model of integrating Sappàya principles to promote elderly self-sufficiency in Doi Saket Subdistrict Municipality, Chiang Mai Province. It was discovered that the integration model should begin at the elderly’s home because the home is considered the center of the entire family. As a result, home improvements do not necessitate extensive structural changes. It should only be replaced in areas prone to frequent accidents, such as stairwells, which should have handrails on both sides, should not be carpeted, and should not have obstacles in the corridor, among other things. The bedroom should be well ventilated, and there should be a light beside the bed. There are handrails, and the color should be obvious. Their restrooms should be wheelchair accessible. Instead of scooping it up with a bowl, they should practice using the shower. Their front doors should be sliding and unlocked from the outside. Temples, parks, markets, and government buildings should all be improved or added to safe facilities with handrails.